Program Perempuan Berdaya Dan Terampil NU CARE LAZISNU Kabupaten Cilacap : Upaya Peningkatan Kapasitas Dan Kemandirian Ekonomi Perempuan - Aji Fany Permana; Lala Febriana Puspita; Slamet Amaludin; Hasa Amalya; Rizki Nazwa Anggita; Atik Nur Chofifah (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The Women's Empowered and Skilled Program is one of the strategic initiatives of NU Care-LAZISNU Cilacap Regency aimed at improving the capacity, skills, and economic independence of women in Cilacap. This article discusses three main sub-programs: the provision of business capital and equipment, women's training and mentoring, and assistance for the renovation of production houses. In addition, this article highlights external collaboration practices that play a key role in the program's success, including a partnership with Indomaret in distributing business carts to 20 women across four districts at the end of 2024. Based on field findings and participant testimonials, the program has proven to have a significant impact on increasing income and empowering women entrepreneurs in the MSME sector. Abstrak Program Perempuan Berdaya dan Terampil merupakan salah satu inisiatif strategis NU Care-LAZISNU Kabupaten Cilacap dalam upaya meningkatkan kapasitas, keterampilan, dan kemandirian ekonomi perempuan di Kabupaten Cilacap. Artikel ini membahas tiga turunan program utama, yaitu pemberian modal usaha dan alat usaha, pelatihan dan pendampingan perempuan, serta bantuan renovasi rumah produksi. Selain itu, artikel ini menyoroti praktik kolaborasi eksternal yang menjadi kunci keberhasilan program, salah satunya kerja sama dengan Indomaret dalam penyaluran gerobak usaha kepada 20 perempuan di empat kecamatan pada akhir tahun 2024. Berdasarkan temuan lapangan dan testimoni peserta, program ini terbukti memberikan dampak signifikan terhadap peningkatan pendapatan dan pemberdayaan perempuan pelaku UMKM.